2018
DOI: 10.1021/acsabm.8b00226
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions Redox Induced Repeatable Nonvolatile Resistive Switching Memory Behavior in Biomaterials

Abstract: The resistance random access memory (RRAM) based on biomaterials has great potential application in the sustainable electronic devices with the advantages of being sustainable, green, and environment-friendly, and it can offer a potential route for developing bio-RRAM devices, which would be a competitive bench in development of multipurpose memory devices. In our work, the banana peel, an ubiquitous useless waste, is introduced as an intermediate insulating material to preparing resistive switching memory dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…57,58 Various biomaterials possess interstitial defects or highly conductive ions that join with active metal ions (top electrode) and to form a stable conduction lament. 17,18,20,24,32,48,49,53 Wang et al reported orange peel extract as a dielectric layer where This work Fig. 7 The complete resistive switching behavior in the pectin-based memristor, where oxygen vacancies act as a hopping charge carrier along with highly conductive Ag 1+ ions leading towards stable CF formation.…”
Section: Pectin-based Memory Cellmentioning
confidence: 86%
See 1 more Smart Citation
“…57,58 Various biomaterials possess interstitial defects or highly conductive ions that join with active metal ions (top electrode) and to form a stable conduction lament. 17,18,20,24,32,48,49,53 Wang et al reported orange peel extract as a dielectric layer where This work Fig. 7 The complete resistive switching behavior in the pectin-based memristor, where oxygen vacancies act as a hopping charge carrier along with highly conductive Ag 1+ ions leading towards stable CF formation.…”
Section: Pectin-based Memory Cellmentioning
confidence: 86%
“…[17][18][19][20]24,32 Many researchers have reported electrochemical redox reactions or valance change mechanisms in biomaterials that depend on the dielectric layer composition. [49][50][51][52][53][54] The electrodes, as well as the defect chemistry of the dielectric layer, play important roles in the resistive switching behavior. 55,56 Surface defect and interfacial engineering of thin lms between the top electrode and the dielectric layer has led to a better understanding of the ohmic and Schottky junction model.…”
Section: Pectin-based Memory Cellmentioning
confidence: 99%
“…Bio-RRAMs are useable in different applications including skin-attached bioelectronics, artificial synapses, biomedical monitoring systems, biotherapy, ultrahigh information storage, artificial intelligence, medical diagnosis, neuromorphic computing, smart wearables, implantable devices, and security purposes owing to their disposability and amenability.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Resistance random access memory (RRAM), owing to its long time reversibly switching between high-resistance states (HRS) and low-resistance states (LRS) under different bias voltages and scan directions, has been considered to be the most prospective candidate for future memory technologies. , Currently, in various aspects of controlling film thickness, designing nanostructures, changing external environment, and test conditions, various materials have been studied in RRAM applications, including binary metal oxides of ZnO, TiO 2 , , , NiO, Cu x O, and HfO 2 , , multiple compounds of Cu 2 ZnSnSe 4 , Cu­(In 1– x Ga x )­Se 2 , and Cu 2 FeSnS 4 , and also heterostructures of MoS 2 /ZnO, BiFeO 3 /Cu 2 ZnSnSe 4 , etc. Though many materials and device designs have been reported and some important conclusions have been obtained to meet the real needs of a faster reading/writing speed, higher storage density, and lower energy consumption in applications, , efforts for designing new structures or materials that possess excellent resistive switching properties are still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The CF evolution is typically correlated with thermal, electrical, and ion migration . Whereas, the conduction mechanism includes the models of Schottky emission, space-charge-limited conduction (SCLC), trap-assisted tunneling, and hopping conduction. , Moreover, the coexistence of RS and NDR was also observed, in which the NDR effect refers to the fact that the abnormal behavior of current decreases with the increase in bias voltage, instead of the commonly higher bias voltage that generates lager current. But so far, although the NDR behavior could appear at room temperature, the observation of the coexistence of resistive switching and negative differential resistance generally needs abnormal conditions, for example, lower temperature and a certain humidity .…”
Section: Introductionmentioning
confidence: 99%